Investigating Students’ Challenges and Solutions in Analyzing Formal University Website Using Multimodal Analysis at A Grammar in Multimodal Discourse Class - Fera Maharani; Soni Tantan Tandiana (SM Institute, 2025)
The development of technology and optimization of digital media has been applied at many levels of education, especially universities. Many services are carried out through digital media, one of which is the formal university website and has received several responses. This is the object of research in one of the courses called Grammar in Multimodal Discourse which in the analysis process reaps challenges. The purpose of this research is to find out the student's challenges and solutions in analyzing a formal university website using multimodal analysis. The research method used in this research was a descriptive case study. The participants consisted of three students majoring in English Education at a university in Tasikmalaya, West Java, Indonesia. The data were collected by using semi-structured interviews. The data were analyzed by thematic analysis. The results showed that the participants faced two challenges, namely: (1) Visual and design challenges and (2) Cognitive and comprehension challenges. There are also three solutions, namely: (1) Seek external support, (2) Independent research, (3) Systematic analysis and comparative evaluation. Therefore, by paying attention to challenges in website analysis, it can improve students' cognitive abilities, create relevant solutions for future analysis progress and can be input for institutions regarding website appearance.